Case report: Findings of automated perimetry during a migraine episode in a patient with glaucoma - Nakakura, Shunsuke; Oogi, Satomi; Tanoue, Asaya; Miyoshi, Teruyuki (Frontiers in Medicine, 2022)
Comorbidities like glaucoma and migraine are often observed among middle-aged individuals, especially women. Herein, we report a rare case of a patient who underwent automated perimetry during a migraine attack. A 52-year-old woman with a 1-year history of blurred vision in the nasal field of her right eye visited Miyoshi Eye Clinic. The intraocular pressures of the right and left eyes were 22 and 24 mm Hg, respectively. Retinal imaging revealed a retinal nerve fiber defect in the temporal superior macula with corresponding thinning of the superior ganglion cell complex in the right eye. The left eye appeared normal. Primary open angle glaucoma was suspected, and the patient underwent visual field examination on the same day. Perimetry showed that the mean deviations in the right and left eyes were -5.00 and -7.68 dB, respectively. A visual field defect in the inferior nasal aspect of the right eye corresponded to the retinal nerve fiber defect. However, right-sided homonymous hemianopia–like visual field defects were observed in both eyes. After the examination, the patient stated that a migraine attack had started 5 min before the examination and continued till after its end (attack duration was ~20 min). In the follow-up examinations without migraine, homonymous hemianopia–like visual field defects disappeared and only a glaucomatous visual field defect in the right eye was observed. Hence, the initial visual field examination findings reflected the effects of a migraine attack alongside glaucoma. Detailed interviews with patients may be beneficial for understanding visual field findings and preventing their untimely examination.